"Vulnerable" resilience: the politics of vulnerability as a self-improvement discourse. Issue 8 (16th November 2020) - Ciccone, Vanessa
ABSTRACT: Resilience has become a central aspect of self-improvement within neoliberal societies. In the present essay, I draw from recent critical scholarship on resilience to investigate vulnerability as an emergent self-improvement discourse. I analyse two popularised videos that profile Brené Brown, a figurehead of vulnerability as a means of resilience-building. I argue that these videos circulate ideas about how to enact "vulnerability, " acting as powerful pedagogical resources that instruct subjects to turn within and work on themselves. Although practicing vulnerability may lead to certain social rewards, it compels subjects to orient their psychic lives toward an individuating sense of self, bringing a myriad of consequences. Below, I assess what is at stake when vulnerability is mobilised as a relational tool located within resilience.